Climatic thresholds associated with increased dengue incidence across climate zones in Peru (2001-2022) - Laura, Wil (2025)
Dengue fever has experienced a global rise in incidence and distribution, largely influenced by climate variability. Nonetheless, the specific climatic thresholds that trigger elevated dengue incidence rates, and the time lag between weather conditions and the case surges remain uncertain. Average weekly climate variables along with weekly dengue incidence rates from 2001 and 2022 were analyzed in districts grouped by its climate zone. A cross-correlation technique was used to determine the time lag between climatic variables and dengue incidence, while a fine-tuned regression tree model was utilized to identify climatic thresholds linked to the incidence of dengue surges.This study identified distinct climatic thresholds that were met within a 20-week window preceding elevated dengue incidence rates in the six climate zones with the highest dengue prevalence in Peru. These insights enable dengue incidence rates forecasting weeks in advance using climatic data, offering a valuable tool for dengue mitigation and early intervention.